ANALISIS PERBANDINGAN FASILITAS JASA TRANSPORTASI KERETA BANDARA DAN BUS DAMRI TERHADAP EFISIENSI PENUMPANG DI BANDARA INTERNASIONAL YOGYAKARTA KULON PROGO - Ayu Gineung Pratidina; Ariyono Setiawan; Totok Warsito (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
ABSTRACT Yogyakarta Special Region has the main airport, Adi Sucipto airport. However, the airport which initially could only accommodate 1.8 million passengers per year was overcapacity to 7.8 million passengers per year. The growth in passenger numbers at Adi Sucipto Airport necessitated the construction of a new New Yogyakarta International Airport (NYIA) in Kulon Progo. This has an impact not only on increasing the number of fleets and flight routes, but also related to the provision of intermodal transportation facilities to and from the airport. Due to the location of the new airport located in Kulon Progo far from the city center and the previous airport, the selection of modes to the new airport did not just happen, public transportation service facilities such as airport trains and damri buses became one of the factors in the selection of modes. This research aims to get the right choice of mode based on the efficiency of service facilities between airport trains and bus damri for passengers who will go to the airport or passengers from the airport to their respective destinations. This Final Task Research uses quantitative descriptive research methods. The preference of choosing the mode between the airport train and the damri bus can be taken into consideration in the decision-making for the improvement of the construction of intermodal facilities to the airport in Kulon Progo.